A role model for all young people living with Asperger. (2nd May 2019) - Lepkowska, Dorothy
Abstract : Swedish school girl Greta Thunberg has inspired the world with her campaign on climate change. However, the fact that Greta is on the autistic spectrum makes her a role model for young people living with the condition across the world, saysDorothy Lepkowska